2022
DOI: 10.1177/14782715221142326
|View full text |Cite
|
Sign up to set email alerts
|

The burden of TB/HIV co-infection among clients attending DOTs clinic in a tertiary centre in Southwestern, Nigeria: A 5-year retrospective study

Abstract: Background: Tuberculosis (TB) and human immunodeficiency virus (HIV) are closely correlated and continue to cause deleterious effects in co-infected patients. This study aimed to determine the prevalence and associated factors of TB/HIV co-infection among directly observed treatment short-course (DOTs) clinic clients in Ogun State, Nigeria. Methods: The TB register and treatment cards of patients that visited the DOTs centre in Federal Medical Centre Abeokuta between January 2015 and December 2019 were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Temitayo-Oboh et al (2022) investigated the prevalence and factors influencing TB and HIV co-infection among patients attending the DOTS clinic in a tertiary health center in Ogun State, Nigeria, between 2015 and 2019. Their study showed that about one in five patients with TB had HIV infection (20% prevalence), which is consistent with our study and that another study reported in Lagos, Nigeria (Adejumo et al, 2017), and higher than the prevalence of 10.9% (Iliyasu and Babashani, 2009), 14.2% (Oladimeji et al, 2013) and 8.4% (Ehondor et al, 2019) reported in similar studies conducted in Kano, Oyo, and Benin City, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temitayo-Oboh et al (2022) investigated the prevalence and factors influencing TB and HIV co-infection among patients attending the DOTS clinic in a tertiary health center in Ogun State, Nigeria, between 2015 and 2019. Their study showed that about one in five patients with TB had HIV infection (20% prevalence), which is consistent with our study and that another study reported in Lagos, Nigeria (Adejumo et al, 2017), and higher than the prevalence of 10.9% (Iliyasu and Babashani, 2009), 14.2% (Oladimeji et al, 2013) and 8.4% (Ehondor et al, 2019) reported in similar studies conducted in Kano, Oyo, and Benin City, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of age, marital status, and occupation, cases of tuberculosis and HIV/AIDS co-infection were highest in those aged 15 to 25 years (443, 30.7%), in married patients (633, 43.9%), and in traders/business owners (731, 50.7%). Temitayo-Oboh et al 4 investigated the prevalence and factors influencing TB and HIV co-infection among patients attending the DOTS clinic in a tertiary health center in Ogun State, Nigeria, between 2015 and 2019. Their study showed that about one in five patients with TB had HIV infection (20% prevalence), which is consistent with our study and that another study reported in Lagos, Nigeria, 14 and higher than the prevalence of 10.9%, 15 14.2% 16 and 8.4% 6 reported in similar studies conducted in Kano, Oyo, and Benin City, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these patients, 672 (2.68%) tested positive for HIV and had TB/HIV coinfection, while the rest of the patients had negative HIV test results. Meanwhile, other studies investigating TB/HIV coinfection have reported different rates of infection, such as a study in Nigeria that reported a 22.50% coinfection rate among TB patients over 5 years [ 30 ], or a study in Kenya, conducted by Wekunda et al that reported a 35.00% coinfection rate [ 31 ]. Another study conducted on HIV/AIDS patients over 18 years of age in Turkey found that 5.30% of these patients had active tuberculosis at the same time [ 32 ], while a study in China, done by Wang et al that examined only EPTB patients reported a 7.00% coinfection rate [ 33 ], compared to 2.00% in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the dominant heterosexual transmission in Ethiopia, vertical transmission from mother to child accounts for more than 90% of pediatric AIDS [18]. In Nigeria, about 69,400 children became infected with HIV through mother-to-child transmission [19,20]. This has led to a rise in the total number of children living with HIV in the country to an unprecedented 440,000 [7].…”
Section: Introductionmentioning
confidence: 99%